Basic Disaster Life Support (BDLS) Training Improves First Responder Confidence to Face Mass-Casualty Incidents in Thailand. Issue 5 (13th June 2017) - Kuhls, Deborah A.; Chestovich, Paul J.; Coule, Phillip; Carrison, Dale M.; Chua, Charleston M.; Wora-Urai, Nopadol; Kanchanarin, Tavatchai
Abstract: Background: Medical response to mass-casualty incidents (MCIs) requires specialized training and preparation. Basic Disaster Life Support (BDLS) is a course designed to prepare health care workers for a MCI. The purpose of this study was to evaluate the confidence of health care professionals in Thailand to face a MCI after participating in a BDLS course. Methods: Basic Disaster Life Support was taught to health care professionals in Thailand in July 2008. Demographics and medical experience were recorded, and participants rated their confidence before and after the course using a five-point Likert scale in 11 pertinent MCI categories. Survey results were compiled and compared with P<.05 statistically significant. Results: A total of 162 health care professionals completed the BDLS course and surveys, including 78 physicians, 70 nurses, and 14 other health care professionals. Combined confidence increased among all participants (2.1 to 3.8; +1.7; P<.001). Each occupation scored confidence increases in each measured area (P<.001). Nurses had significantly lower pre-course confidence but greater confidence increase, while physicians had higher pre-course confidence but lower confidence increase. Active duty military also had lower pre-course confidence with significantly greater confidence increases, while previous disaster courses or experience increased pre-course confidence but lower increase in confidence. Age and work experience did not influence confidence. Conclusion: Basic Disaster Life Support significantly improves confidence to respond to MCI situations, but nurses and active duty military benefit the most from the course. Future courses should focus on these groups to prepare for MCIs. DA Kuhls, PJ Chestovich, P Coule, DM Carrison, CM Chua, N Wora-Urai, T Kanchanarin .Basic Disaster Life Support (BDLS) training improves first responder confidence to face mass-casualty incidents in Thailand .Prehosp Disaster Med .2017 ;32 (5 ):492 –500 .